Life and words : violence and the descent into the ordinary - Das, Veena (Philip E. Lilienthal Asian studies imprint., 2007)
In this powerful, compassionate work, one of anthropology's most distinguished ethnographers weaves together rich fieldwork with a compelling critical analysis in a book that will surely make a signal contribution to contemporary thinking about violence and how it affects everyday life. Veena Das examines case studies including the extreme violence of the Partition of India in 1947 and the massacre of Sikhs in 1984 after the assassination of then Prime Minister Indira Gandhi. In a major departure from much anthropological inquiry, Das asks how this violence has entered "the recesses of the ord.